Impaired fertility and motor function in a zebrafish model for classic galactosemia. Issue 1 (14th September 2017) - Vanoevelen, Jo M.; van Erven, Britt; Bierau, Jörgen; Huang, Xiaoping; Berry, Gerard T.; Vos, Rein; Coelho, Ana I.; Rubio‐Gozalbo, M. Estela
Abstract: Classic galactosemia is a genetic disorder of galactose metabolism, caused by severe deficiency of galactose‐1‐phosphate uridylyltransferase (GALT) enzyme activity due to mutations of the GALT gene. Its pathogenesis is still not fully elucidated, and a therapy that prevents chronic impairments is lacking. In order to move research forward, there is a high need for a novel animal model, which allows organ studies throughout development and high‐throughput screening of pharmacologic compounds. Here, we describe the generation of a galt knockout zebrafish model and present its phenotypical characterization. Using a TALEN approach, a galt knockout line was successfully created. Accordingly, biochemical assays confirm essentially undetectable galt enzyme activity in homozygotes. Analogous to humans, galt knockout fish accumulate galactose‐1‐phosphate upon exposure to exogenous galactose. Furthermore, without prior exposure to exogenous galactose, they exhibit reduced motor activity and impaired fertility (lower egg quantity per mating, higher number of unsuccessful crossings), resembling the human phenotype(s) of neurological sequelae and subfertility. In conclusion, our galt knockout zebrafish model for classic galactosemia mimics the human phenotype(s) at biochemical and clinical levels. Future studies in our model will contribute to improved understanding and management of this disorder.